2007
DOI: 10.1159/000103307
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Neural RNA-Binding Protein Musashi1 in Pediatric Brain Tumors

Abstract: Musashi1 (MSI1) is an evolutionarily conserved RNA-binding protein, selectively expressed in neural stem cells (NSCs) and considered a versatile marker for normal NSCs and tumor cell diagnosis. Here, we examined MSI1 expression in primary pediatric brain tumors, medulloblastomas and ependymomas, by double immunostaining with lineage phenotypic markers (Lin). These tumors highly express MSI1 and are heterogeneous, containing both MSI1+/Lin– tumor cells in regions of relatively high cellularity and proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 39 publications
1
26
0
Order By: Relevance
“…Msi-1 is an RNA binding protein which is preferentially expressed in stem-cells, functions as a translational repressor (56)(57)(58), and is widely used as a molecular marker to identify stem cells in embryos and adult tissues (26)(27)(28)(29). In our study, Msi-1 was expressed in five MRT cell lines except TTC642, which originated from a neck mass.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Msi-1 is an RNA binding protein which is preferentially expressed in stem-cells, functions as a translational repressor (56)(57)(58), and is widely used as a molecular marker to identify stem cells in embryos and adult tissues (26)(27)(28)(29). In our study, Msi-1 was expressed in five MRT cell lines except TTC642, which originated from a neck mass.…”
Section: Discussionmentioning
confidence: 69%
“…In recent years, the concept of CSC involvement in tumorigenesis has attracted the attention of many researchers. Previous studies have shown that NSC acting as CSC is recognized in CNS (24)(25)(26)(27)(28)(29). In the present study, we examined the expression of NSC markers such as CD133, nestin and Msi-1 before and after 4-HPR induced differentiation in MRT cell lines to elucidate the cytological characteristics of MRT cells that are considered to derive from neuroectodermal origin (8,9,12).…”
Section: Introductionmentioning
confidence: 95%
“…MSI1 is expressed predominantly in proliferating multipotent neural precursor cells, but not in newly generated postmitotic neurons (35). Nakano et al (36) examined MSI1 expression in human medulloblatomas and ependymomas, suggesting that MSI1 could be a useful marker for characterizing tumor heterogeneity and for examining the analogy between normal NSCs and MSI1 + cells in pediatric brain tumors.…”
Section: Discussionmentioning
confidence: 99%
“…A disease of great relevance to Msi1 is cancer, because many carcinoma cells are of epithelial stem cell lineage (48), expressing Msi1 protein. Strong expression of the Msi1 protein has been observed in many tumors, such as glioma (25), hepatoma (26), colorectal adenoma (27,49), teratoid/rhabdoid tumors in eye (50), non-small cell lung cancer (51), retinoblastoma (52), medulloblastoma (53,54), ependymoma (53), endometrial carcinoma (55), neurocytoma (56), glioblastoma (57), cervical carcinoma (58), etc. Although the exact function of Msi1 in these cancer cells remains unclear, knockdown of Msi1 by using siRNA resulted in tumor growth arrest in colon adenocarcinoma xenografts transplanted in athymic nude mice, reduced cancer cell proliferation, and increased apoptosis (59).…”
Section: Msi1 and Diseasesmentioning
confidence: 99%